Advanced Free Vortex Wake Method For Variable Rpm Rotors - Chen, Y.; Khodaparast, H. H.; Celik, A.; Yuan, Y. (My University, 2025)
Free vortex wake (FVW) method is widely used for aerodynamic calculation of rotor systems, as it strikes a balance between accuracy and efficiency in rotorcraft flight dynamics and handling qualities analysis. However, limitations such as inaccuracy in the reverse flow region calculations in the FVW method prevents its application in variable RPM (VRPM) rotors. In this paper, the authors introduce several improvements to the current FVW method, including planar rigid near-wake reverse flow correction and improved far-wake generation method, enabling it for VRPM rotor simulations. The results obtained with the improved FVW method are compared against experimental data and show good agreement.